158k views
5 votes
How is the graph of y=2(3)^x-1+4 translated from the graph of y=2(3)^x?

User Qbyte
by
4.7k points

2 Answers

4 votes

f(x - n) - shift the graph n units right

f(x + n) - shift the graph n units left

f(x) - n - shift the graph n units down

f(x) + n - shift the graph n units up ----------------------------------------------------------------------------


y=2(3)^x\\\\y=2(3)^(x-1)+4

Answer: shift the graph of y = 2(3)ˣ one unit right and four units up.

User Michael Landes
by
5.2k points
4 votes

Answer:

The rule of translation is:

  • 1 units to the right and 4 units upward.

Explanation:

We know that if the function f(x) is translated k units to the right or left by k units if:

f(x) → f(x+k)

if k>0 then it is shifted k units to the left

and if k<0 then it is shifted k units to the right.

Also, the translation:

f(x) →f(x)+k

is a translation k units upward if k>0

and k units downward if k<0

The parent function is given by:


y=2\cdot 3^x

The translated function:


y=2\cdot 3^(x-1)+4

is a translation of the parent function 1 units to the right and 4 units upwards.

User Sofien Rahmouni
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.